Perancangan Sistem Informasi Penjualan Handphone pada toko Raja Ponsel Cikarang dengan Menggunakan Metode SWOT - Agus Hidayat; Mayadi; Muhammad khaerudin (Journal of Informatic and Information Security, 2023)
Information Technology continues to grow along with the ability of computers to provide solutions to problems in sharing areas. One of the depelopment of information technology is the existence of information systems that can provide solutions for the sales process. At Toko Raja Ponsel, the author pay attention to the transactions conducted in the store of the king of mobile phones are still done manually, recording sales reports, reports data items are still recorded in the book so that data can be lost and damaged. In this study describes what matters are the factors of making the information system of mobile phone sales, and what is needed in the making. From the description the authors analyzed the existing system in the Toko Raja Ponsel by using SWOT analysis, so found a solution to the problem solving that is with the development of products that received a rating of 19.7 attractiveness of the total number of respondents. From these results the authors developed a system with UML (unified modeling language) with user interfaces Microsoft Visual Studio 2010 and My Sql as its database. With this writer provide solution of making information system of sale, hence can assist in every transaction, so give ease in every transaction more effective and efficient.